Cathode active material, preparation method thereof and secondary battery
By covering two active materials with the same ion conductor, the problem of uneven interface transmission of the positive electrode active material in lithium-ion batteries is solved, which significantly improves the transmission consistency and uniformity of lithium ions and improves the electrochemical performance of the battery.
Patent Information
- Application Number
- CN202311388245.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-24
- Publication Date
- 2025-04-25
AI Technical Summary
In existing lithium-ion batteries, different types of positive electrode active materials have differences in energy density, safety and cost, and the interface transmission of different materials is uneven, resulting in poor electrochemical performance.
By covering two active materials with the same ion conductor, the ion transmission rate at the material interface is improved and the transmission consistency and uniformity of lithium ions are improved. Specifically, the first active material and the second active material each include a matrix and a coating layer containing a compound containing yttrium and tungsten, such as LiYW2O8, LiYO2 or Li2WO4.
Through the use of the cladding layer, the surface stability of the material is improved, side reactions are suppressed, the migration rate and electrochemical performance of lithium ions are improved, and the overall performance of lithium ion batteries is significantly improved.
Smart Images

Figure CN119890244A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium battery materials, and in particular to a positive electrode active material and a preparation method thereof and a secondary battery. Background Art
[0002] With the rapid development of electric vehicles, the requirements for lithium-ion batteries are getting higher and higher. As one of the key factors affecting the electrochemical performance of lithium-ion batteries, positive electrode active materials have attracted widespread attention from R&D workers. Different types of positive electrode active materials have certain differences in energy density, safety, cost, etc. Sometimes, in order to take into account the advantages of different active material systems, several active materials are selected and mixed for use at the same time, but the interaction between the two active materials may also have an adverse effect on the electrochemical performance. At the same time, because the interface consistency of the two active materials is often low, there is a large difference in ionic conductivity and electronic conductivity, the interface transmission of lithium ions and electrons is prone to unevenness, resulting in poor system consistency. Summary of the invention
[0003] In response to the problems existing in the prior art, the present application provides a positive electrode active material comprising two active materials coated with the same ion conductor, thereby achieving complementary advantages of the two active materials while improving the ion transfer rate at the interface of the two active material particles, enhancing the consistency and uniformity of lithium ion transfer, and improving the electrochemical performance of lithium-ion batteries.
[0004] The present application provides a positive electrode active material, which includes a first active material, wherein the first active material includes a first substrate and a first coating layer coated on the surface of the first substrate; and a second active material, wherein the second active material includes a second substrate and a second coating layer coated on the surface of the second substrate, and the first coating layer and the second coating layer include the same ion conductor.
[0005] The present invention coats the first active material and the second active material to reduce the contact between the two and the electrolyte, improve the surface stability of the material, inhibit the side reaction between the active material and the electrolyte, and improve the mutual influence at the interface of the two active materials; because the ion conductor has good lithium ion conductivity, the migration rate of lithium ions on the material surface can be increased, which is beneficial to the insertion and extraction of lithium ions during the charge and discharge process; at the same time, the same ion conductor is used to coat the first active material and the second active material respectively, which promotes the movement and transmission of lithium ions between the interfaces of the two active materials, significantly improves the disadvantage of low conductivity of point-to-point particle contact of the two active materials, and improves the electrochemical performance of lithium ion batteries.
[0006] In one aspect of the present disclosure, the ion conductor includes a compound containing at least one of yttrium and tungsten.
[0007] In the present application, the compound including at least one of yttrium and tungsten has higher structural stability, and the tungsten or yttrium contained in the coating layer improves the conductivity of the lithium transition metal oxide and the surface stability of the material, reduces the side reaction between the positive electrode material and the electrolyte and can effectively improve the gas production problem, and also promotes the diffusion of lithium ions and improves the cycle performance.
[0008] In one aspect of the present application, the ion conductor comprises LiYW2O8, LiYO2 or Li2WO4.
[0009] In one aspect of the present application, the first matrix comprises a lithium transition metal oxide of the following chemical formula 1, and the second matrix comprises a lithium phosphate compound of the following chemical formula 2:
[0010] Chemical formula 1: LiNi a Co b Mn c M 1 d O2
[0011] Where a+b+c+d=1, 0.50≤a≤1, 0≤b≤0.40, 0≤c≤0.50, 0≤d≤0.10, M 1 At least one selected from the group consisting of Al, B, Sr, Y, Ba, W, Ca, Cu, Fe, V, Cr, Ti, Zr, Zn, In, Ta, La, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg and Mo;
[0012] Chemical formula 2: LiFe 1-x1 M 2 x1 PO4
[0013] Among them, 0≤x1≤0.7, M 2 At least one selected from Cu, Mn, Cr, Zn, V, Pb, Ca, Co, Ni, Sr or Ti.
[0014] The present invention coats lithium transition metal oxide and lithium iron phosphate to reduce the contact between the two and the electrolyte, improves the adverse effect of residual alkali on the surface of lithium transition metal oxide on lithium iron phosphate, especially on lithium transition metal oxide positive electrode active materials with high nickel content, and at the same time, the coating of lithium iron phosphate can reduce the dissolution of iron, and at the same time can reduce the influence of more magnetic foreign matter in lithium iron phosphate on lithium transition metal oxide, and inhibit the mutual adverse effect and side reaction between the two. At the same time, the ionic conductivity of lithium iron phosphate and lithium transition metal oxide is quite different, and the ionic conductor coated with the same material can promote the movement and transmission of lithium ions between the interface of lithium transition metal oxide and lithium iron phosphate system when the mixed system is used, solves the problem of low conductivity when lithium transition metal oxide and lithium iron phosphate system are in point-to-point particle contact, and improves the electrochemical performance of lithium ion batteries.
[0015] In one aspect of the present application, the first coating layer has a thickness of 2 nm to 8 nm, and / or the second coating layer has a thickness of 2 nm to 8 nm.
[0016] The present application achieves the purpose of inhibiting the side reaction between the material surface and the electrolyte by setting a suitable coating layer thickness while ensuring the lithium ion transmission performance. That is, if the thickness of the first coating layer and the second coating layer is too thick, the diffusion rate of lithium ions will be reduced, resulting in a decrease in the capacity and rate performance of the material, and it will also cause unnecessary waste of raw materials and increase costs; when the coating layer thickness is too small, the side reaction between the material surface and the electrolyte cannot be effectively inhibited.
[0017] In one aspect of the present application, the thickness of the first coating layer is less than the thickness of the second coating layer. In one aspect of the present application, the thickness of the first coating layer is 2nm to 5nm, and the thickness of the second coating layer is 4nm to 8nm.
[0018] Since the second active material, such as lithium iron phosphate or lithium manganese iron phosphate, has a poorer conductivity, the second active material coating layer is thicker to obtain better ionic conductivity.
[0019] In one aspect of the present application, the mass ratio of the first active material to the second active material is (80-90):(10-20).
[0020] In one aspect of the present application, the particle size Dv50 of the first active material is 10 μm to 20 μm, and / or the Dv50 of the second active material is 0.6 μm to 1.5 μm.
[0021] The present application provides a secondary battery, which includes the above-mentioned positive electrode active material.
[0022] The present application provides a method for preparing the aforementioned positive electrode active material, the method comprising the following steps:
[0023] S1: providing a first active material and a second active material respectively, wherein the first active material comprises a first substrate and a first coating layer coated on a surface of the first substrate; the second active material comprises a second substrate and a second coating layer coated on a surface of the second substrate, and the first coating layer and the second coating layer comprise the same ion conductor;
[0024] S2: Mix the first active material and the second active material in a mass ratio (80-90):
[0025] The positive electrode active material is obtained by mixing the two materials in a ratio of (10-20). BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The TEM image of the positive electrode active material obtained in Example 1 is shown; DETAILED DESCRIPTION
[0027] In order to make the purpose, technical scheme and advantages of the present application clearer, the technical scheme of the present application will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The relevant embodiments described herein are illustrative and are used to provide a basic understanding of the present application. The embodiments of the present application should not be interpreted as limiting the present application.
[0028] the term:
[0029] For simplicity, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.
[0030] In this article, the terms "comprises", "comprising" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device that includes a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of more restrictions, an element defined by the sentence "comprising a ..." does not exclude the presence of other identical elements in the process, method, article or device that includes the element.
[0031] In this document, it is necessary to understand that the orientations or positional relationships indicated by terms such as “upper”, “lower”, “top”, “bottom”, “inside” and “outside” are based on the orientations or positional relationships shown in the accompanying drawings and are only for the convenience of describing the present invention and simplifying the description. They do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.
[0032] In the description herein, unless otherwise specified, “above” and “below” include the number.
[0033] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).
[0034] The term "about" is used to describe and illustrate small changes. When used in conjunction with an event or situation, the term may refer to an example in which the event or situation occurs precisely and an example in which the event or situation occurs very approximately. For example, when used in conjunction with a numerical value, the term may refer to a range of variation of less than or equal to ±10% of the numerical value, such as less than or equal to ±5%, less than or equal to ±4%, less than or equal to ±3%, less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.1%, or less than or equal to ±0.05%. In addition, amounts, ratios, and other numerical values are sometimes presented in this article in a range format. It should be understood that such a range format is for convenience and simplicity, and should be flexibly understood to include not only numerical values explicitly designated as range limits, but also all individual numerical values or subranges encompassed within the range, as if each numerical value and subrange were explicitly designated.
[0035] A list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.
[0036] The term Dv50 is the particle size corresponding to 50% of the cumulative particle size distribution in the positive electrode active material based on a volume basis, that is, the median particle size.
[0037] NCM811 and NCM955 refer to nickel-cobalt-manganese ternary positive electrode active materials, in which the molar ratios of the three elements of nickel, cobalt and manganese are 80:10:10 and 90:5:5 respectively.
[0038] The present application is further described below in conjunction with specific implementations. It should be understood that these specific implementations are only used to illustrate the present application and are not used to limit the scope of the present application. Specific implementation method:
[0040] Positive electrode:
[0041] In some embodiments of the present application, the positive electrode plate includes a positive current collector and a positive active material coated on the positive current collector. In the present application, the positive active material includes a first active material, the first active material includes a first substrate and a first coating layer coated on the surface of the first substrate; a second active material, the second active material includes a second substrate and a second coating layer coated on the surface of the second substrate, and the first coating layer and the second coating layer include the same ion conductor.
[0042] In some embodiments of the present application, the ion conductor includes a compound containing at least one of yttrium and tungsten.
[0043] In some embodiments of the present application, the ion conductor includes LiYW2O8, LiYO2 or Li2WO4.
[0044] In some embodiments of the present application, the first matrix has a lithium transition metal oxide of the following Chemical Formula 1, and the second matrix has a lithium phosphate compound of the following Chemical Formula 2:
[0045] Chemical formula 1: LiNi a Co b Mn c M 1 d O2
[0046] Where a+b+c+d=1, 0.50≤a≤1, 0≤b≤0.40, 0≤c≤0.50, 0≤d≤0.10, M 1 At least one selected from the group consisting of Al, B, Sr, Y, Ba, W, Ca, Cu, Fe, V, Cr, Ti, Zr, Zn, In, Ta, La, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg and Mo;
[0047] Chemical formula 2: LiFe 1-x1 M 2 x1 PO4
[0048] Among them, 0≤x1≤0.7, M2 At least one selected from Cu, Mn, Cr, Zn, Pb, Ca, Co, V, Ni, Sr or Ti.
[0049] In some embodiments of the present application, the first matrix includes at least one of lithium nickel oxide, lithium nickel cobalt oxide, lithium nickel manganese oxide, and lithium nickel cobalt manganese oxide.
[0050] In some embodiments of the present application, the first substrate is a lithium nickel cobalt manganese ternary active material. Preferably, the molar content of nickel in the lithium nickel cobalt manganese ternary active material accounts for more than 60% of the total molar content of transition metal elements. For example, the first substrate is NCM811 or NCM955. As the nickel content in the lithium transition metal oxide increases, the side reaction between the surface of the positive electrode active material and the electrolyte intensifies, so coating it can effectively improve the surface stability of the positive electrode active material. The second active material is a lithium iron phosphate active material or a lithium iron manganese phosphate active material.
[0051] In some embodiments of the present application, the first coating layer has a thickness of 2nm to 8nm, and / or the second coating layer has a thickness of 2nm to 8nm. Preferably, the first coating layer has a thickness of 2nm to 5nm, and / or the second coating layer has a thickness of 4nm to 8nm.
[0052] In some embodiments of the present application, the thickness of the first cladding layer is less than the thickness of the second cladding layer. In some embodiments of the present application, the thickness of the first cladding layer is 4 nm, and the thickness of the second cladding layer is 5 nm.
[0053] In some embodiments of the present application, the mass ratio of the first active material to the second active material is: (80-90):(10-20). In some embodiments of the present application, the ratio may be, for example, 80:20, 85:15 or 90:10.
[0054] In some embodiments of the present application, the Dv50 of the first active material is 10 μm to 20 μm, and / or the Dv50 of the second active material is 0.6 μm to 1.5 μm.
[0055] In some embodiments of the present application, the positive electrode active material further includes a binder, and optionally also includes a conductive material. The binder improves the bonding between the positive electrode active material particles and also improves the bonding between the positive electrode active material and the current collector.
[0056] In some embodiments of the present application, the positive electrode current collector may be aluminum (Al), but is not limited thereto.
[0057] In some embodiments of the present application, the positive electrode active material is prepared by the following method:
[0058] S1: providing a first active material and a second active material respectively, wherein the first active material comprises a first substrate and a first coating layer coated on a surface of the first substrate; the second active material comprises a second substrate and a second coating layer coated on a surface of the second substrate, and the first coating layer and the second coating layer comprise the same ion conductor;
[0059] S2: Mix the first active material and the second active material in a mass ratio of (80-90):(10-20) to obtain the positive electrode active material.
[0060] In some embodiments of the present application, the first matrix is a nickel-cobalt-manganese ternary active material, and the second matrix is a lithium iron phosphate active material.
[0061] In the step S1, a nickel-cobalt-manganese ternary active material precursor, a lithium source, and a tungsten source and / or a yttrium source are mixed and calcined to obtain the first active material;
[0062] The lithium source, iron phosphate, and tungsten source and / or yttrium source are mixed and calcined to obtain the second active material.
[0063] The nickel-cobalt-manganese ternary active material precursor can be obtained by a preparation method known in the art, and the present application does not impose any limitation on the preparation method of the precursor.
[0064] In some embodiments of the present application, the tungsten source is tungstic acid, and the yttrium source is yttrium nitrate.
[0065] Negative electrode:
[0066] In some embodiments of the present application, the lithium-ion battery provided in the present application further includes a negative electrode plate, and the negative electrode plate includes a current collector and a negative electrode active material disposed on the current collector. The specific types of negative electrode active materials are not subject to specific restrictions and can be selected according to needs. Specifically, the negative electrode active material is selected from natural graphite, artificial graphite, mesophase microcarbon beads (referred to as MCMB), hard carbon, soft carbon, silicon, silicon-carbon composites, Li-Sn alloys, Li-Sn-O alloys, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 , one or more of Li-Al alloys.
[0067] In some embodiments of the present application, the negative electrode active material may include a binder and optionally a conductive material. The binder improves the bonding between the negative electrode active material particles and the bonding between the negative electrode active material and the current collector.
[0068] In some embodiments of the present application, the negative electrode sheet of the present application includes a negative electrode active material, a binder and a conductive agent.
[0069] In some embodiments of the present application, the negative electrode active material of the present application may also be selected from other materials that can electrochemically absorb and release metal ions such as lithium ions. Specifically, it can be selected from carbonaceous materials, silicon materials, alloy materials, lithium-containing metal oxide materials, etc. They can be used alone or in any combination of two or more.
[0070] In some embodiments of the present application, the negative electrode current collector may be selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof.
[0071] Diaphragm:
[0072] In some embodiments of the present application, the lithium ion battery and electrochemical device of the present application are provided with a separator between the positive electrode and the negative electrode to prevent short circuit. The material and shape of the separator used in the electrochemical device of the present application are not particularly limited, and it can be any technology disclosed in the prior art.
[0073] In some embodiments of the present application, the separator includes a polymer or an inorganic substance formed of a material that is stable to the electrolyte of the present application.
[0074] In some embodiments of the present application, the separator may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film having a porous structure.
[0075] Electrolyte:
[0076] The lithium-ion battery and electrochemical device involved in the present application also include an electrolyte, and the electrolyte can be the electrolyte used in the prior art in the field.
[0077] In some embodiments, the electrolyte includes a lithium salt and a solvent.
[0078] In some embodiments, the electrolyte may optionally include additives.
[0079] Secondary battery:
[0080] In some embodiments of the present application, the secondary battery involved in the present application includes the above-mentioned positive electrode plate, negative electrode plate, separator, electrolyte, etc., but is not limited thereto.
[0081] In some embodiments of the present application, the secondary battery involved in the present application may include an outer package, which may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the secondary battery may also be a soft package, such as a bag-type soft package.
[0082] In some embodiments, the present application also provides a battery module. The battery module includes the above-mentioned secondary battery. The battery module of the present application uses the above-mentioned secondary battery, and therefore has at least the same advantages as the secondary battery. The number of secondary batteries contained in the battery module of the present application can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.
[0083] In some embodiments, the present application further provides a battery pack, which includes the above-mentioned battery module. The number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.
[0084] Device:
[0085] The present application also provides a device, which includes at least one of the above-mentioned secondary battery, battery module or battery pack.
[0086] In some embodiments, the device includes, but is not limited to: electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, power storage systems, etc. In order to meet the device's requirements for high power and high energy density of lithium-ion batteries, a battery pack or battery module may be used.
[0087] In other embodiments, the device may be a mobile phone, a tablet computer, a laptop computer, etc. The device is usually required to be thin and light, and a lithium-ion battery may be used as a power source.
[0088] The present application is further described below in conjunction with the examples. It should be understood that these examples are only used to illustrate the present application and are not used to limit the scope of the present application.
[0089] Examples and Comparative Examples
[0090] Embodiment 1:
[0091] Preparation of positive electrode active materials:
[0092] The positive electrode active material of Example 1 includes: LiNi having a LiYW2O8 coating layer 0.90 Co 0.05 Mn 0.05 The ternary material (abbreviated as NCM) has a coating layer thickness of 2nm, and the LiFePO4 material with a LiYW2O8 coating layer (abbreviated as LFP) has a coating layer thickness of 2nm. The specific preparation method is as follows:
[0093] Ni 0.90 Co 0.05 Mn 0.05The (OH)2 precursor, lithium hydroxide, yttrium nitrate, and tungstic acid were mixed evenly in a molar ratio of 1:1.03:0.005:0.01, and then transferred to an atmosphere furnace, pre-burned at 450°C for 3h under an oxygen atmosphere, and then calcined at 750°C for 12h under oxygen to obtain a coated ternary material.
[0094] Li2CO3, FePO4, yttrium nitrate and tungstic acid were mixed evenly in a molar ratio of 1.02:1:0.005:0.01, and then transferred to an atmosphere furnace, pre-burned at 350°C for 3 hours under a nitrogen atmosphere, and then calcined at 720°C for 8 hours under nitrogen to obtain a coated lithium iron phosphate material.
[0095] The above ternary material and lithium iron phosphate material were mixed in a mass ratio of 85:15 to obtain the positive electrode active material of Example 1.
[0096] Examples 2 to 10 and Comparative Examples 1 to 5
[0097] The preparation process of the positive electrode active materials of Examples 2 to 10 and Comparative Examples 1 to 5 is basically the same as that of Example 1, except for the type of coating material, the thickness of the coating layer, the Dv50 particle size of the two active materials, and the mass ratio. For example, by controlling the amount of the positive electrode active material added during the preparation process, coating layers of different thicknesses are obtained. The specific differences are shown in Table 1.
[0098] Preparation of button cells:
[0099] The above positive electrode material, conductive carbon black (Super-P), and binder polyvinylidene fluoride (PVDF) were mixed in an N-methylpyrrolidone (NMP) solvent system at a weight ratio of 90:5:5, and then coated on aluminum foil to control the coating mass to 10 mg / cm 2 Up to 30mg / cm 2 , dried at 105°C, cold pressed, and punched to obtain the positive electrode sheet; the positive electrode sheet, isolation membrane, and metal lithium sheet were placed in a button battery steel shell in order, and an appropriate amount of electrolyte (1M LiPF6, EC:EMC:DEC volume ratio of 1:1:1) was dripped into it, and the button battery was obtained after sealing.
[0100] Electrochemical testing:
[0101] High temperature storage performance:
[0102] The assembled CR2025 button cell was charged to 4.2V at 0.1C charging current, and the capacity was recorded as C1. It was placed at 45℃ for 14 days. Then it was discharged to 2.0V at 0.1C discharge current, and the capacity was C2. C2 / C1 was used to obtain the high temperature storage capacity retention rate.
[0103] High temperature cycle capacity retention rate:
[0104] At 45°C, the button battery was first charged at 0.5C constant current to 4.2V, and then discharged at 1C to 2.0V to complete one cycle. The above procedure was repeated for 300 cycles to obtain the cycle capacity retention rate.
[0105] The button cells of the embodiment and the comparative example were subjected to electrochemical tests to test their high temperature storage performance and cycle capacity retention rate, respectively. The obtained data are shown in Table 1.
[0106] [Table 1]
[0107]
[0108]
[0109] It can be seen that compared with comparative examples 1-5, embodiments 1-10 exhibit better high-temperature storage and cycle performance, indicating that the simultaneous coating of lithium transition metal oxide positive electrode materials and lithium iron phosphate positive electrode materials can significantly inhibit the side reactions of the electrolyte with the lithium transition metal oxide positive electrode materials and lithium iron phosphate, and that ion conductors coated with the same substance can promote the movement and transmission of lithium ions between the interfaces of lithium transition metal oxide and lithium iron phosphate when the mixed system is used, thereby solving the problem of low conductivity when lithium transition metal oxide and lithium iron phosphate particles are in point-to-point contact, and improving the electrochemical performance.
[0110] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limitations on the present application, and that changes, substitutions and modifications may be made to the embodiments without departing from the spirit, principles and scope of the present application.
Claims
1. A positive electrode active material, characterized in that: The positive electrode active material comprises: a first active material, wherein the first active material comprises a first substrate and a first coating layer coated on the surface of the first substrate, A second active material, wherein the second active material comprises a second substrate and a second coating layer coated on a surface of the second substrate, The first cladding layer and the second cladding layer include the same ion conductor.
2. The positive electrode active material according to claim 1, characterized in that The ion conductor includes a compound containing at least one of yttrium and tungsten.
3. The positive electrode active material according to claim 2, characterized in that The ion conductor includes LiYW2O8, LiYO2 or Li2WO4.
4. The positive electrode active material according to any one of claims 1 to 3, characterized in that The first coating layer has a thickness of 2 nm to 8 nm, and / or the second coating layer has a thickness of 2 nm to 8 nm.
5. The positive electrode active material according to claim 1, characterized in that The first matrix is a lithium transition metal oxide having a chemical formula 1, and the second matrix is a lithium phosphate compound having a chemical formula 2, Chemical formula 1: LiNi a Co b Mn c M 1 d O2 Where a+b+c+d=1, 0.50≤a≤1, 0≤b≤0.40, 0≤c≤0.50, 0≤d≤0.10, M 1 At least one selected from the group consisting of Al, B, Sr, Y, Ba, W, Ca, Cu, Fe, V, Cr, Ti, Zr, Zn, In, Ta, La, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg and Mo; Chemical formula 2: LiFe 1-x1 M 2 x1 PO4 Among them, 0≤x1≤0.7, M 2 At least one selected from Cu, Mn, Cr, V, Zn, Pb, Ca, Co, Ni, Sr or Ti.
6. The positive electrode active material according to claim 5, characterized in that The mass ratio of the first active material to the second active material is (80-90):(10-20).
7. The positive electrode active material according to claim 5, characterized in that The Dv50 of the first active material is 10 μm to 20 μm, and / or the Dv50 of the second active material is 0.6 μm to 1.5 μm.
8. The positive electrode active material according to claim 5, characterized in that The thickness of the first cladding layer is 2nm-5nm, and the thickness of the second cladding layer is 4nm-8nm.
9. A secondary battery, characterized in that: The invention comprises the positive electrode active material as claimed in claims 1 to 8.
10. A method for preparing the positive electrode active material according to claims 1 to 9, characterized in that: The method comprises the following steps: S1: providing a first active material and a second active material respectively, wherein the first active material comprises a first substrate and a first coating layer coated on a surface of the first substrate; the second active material comprises a second substrate and a second coating layer coated on a surface of the second substrate, and the first coating layer and the second coating layer comprise the same ion conductor; S2: Mix the first active material and the second active material in a mass ratio (80-90): The positive electrode active material is obtained by mixing the two materials in a ratio of (10-20).